Beyond Appearances: Unveiling the Disconnect Between Governance and Legitimacy in López Obradors Government (2018-2024) in Mexico (Global Journal of Human-Social Science, 2025)
This article examines the complex relationship between governance and legitimacy during Andr s Manuel L pez Obrador s administration in Mexico 2018-2024 Using a mixed-methods approach it analyzes the evolution of governance indicators and popular support considering how high levels of legitimacy have persisted despite weak governance This persistence is partly attributed to presidential charisma the low political culture of Mexicans and social welfare policies The study reviews theoretical frameworks on legitimacy and governance assessing the apparent disconnect between these concepts in the Mexican context Additionally it proposes possible explanations for this paradox and suggests avenues for future research on how social and political factors influence public perceptions of government performance
Keywords: governance; political legitimacy; mexico; government effectiveness